Businessman ethos and image: review and comparison of research from Portugal and Poland - Swiatkiewicz, Olgierd (Society Register, 2024)
The article examines research on the ethos and image of the businessman in Portugal and Poland, using a comparative and diachronic analysis, resorting to secondary sources and critical analysis of the literature. The purpose of the research determined the descriptive character of the work. After defining the concept of ethos, its functions, and models, the article briefly describes the milestones in the contemporary history of both countries, characterizes the national/organizational cultures and presents the image and ethos of the businessman in each country. In conclusion, attention was drawn to the common and differentiating elements of the ethos and image of the businessman in both countries.